2015
DOI: 10.1063/1.4915913
|View full text |Cite
|
Sign up to set email alerts
|

Formation of low-frequency harmonics on the surface of liquid hydrogen and helium in a turbulent regime

Abstract: The formation of harmonics at frequencies below a monochromatic pump frequency in a system of capillary-gravity waves on surfaces of liquid hydrogen and superfluid helium in a turbulent regime is studied experimentally. By choosing the spectral characteristics of the exciting force and the resolution in the spectrum of the surface oscillations, it is possible to create conditions for low-frequency wave generation by changing the boundaries of the experimental cell. For certain monochromatic pump frequencies, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…These experiments provided means to compare with the theoretical predictions and against numerical simulations [613,626,627]. Finally, we note that evidence for a split energy cascade has been observed in gravito-capilary turbulence [96,97] on the surface of liquid Helium. A recent review of these experimental results can be found in [628].…”
Section: Gravito-capillary Surface Wavesmentioning
confidence: 52%
See 1 more Smart Citation
“…These experiments provided means to compare with the theoretical predictions and against numerical simulations [613,626,627]. Finally, we note that evidence for a split energy cascade has been observed in gravito-capilary turbulence [96,97] on the surface of liquid Helium. A recent review of these experimental results can be found in [628].…”
Section: Gravito-capillary Surface Wavesmentioning
confidence: 52%
“…Similar behaviour has been attributed to astrophysical flows (like the atmosphere of Venus and Jupiter [88,89], and accretion discs [90]), in plasma flows [91] and in industrial applications (like in tokamak [92]) either due to the thinness of the layer, to fast rotation or to the presence of strong magnetic fields. Split cascades have also been observed in wave systems [93], multi-scale optical turbulence [94], acoustic turbulence [95] and capillary turbulence on the surface of liquid hydrogen and helium [96,97]. In many of these systems, a change from a split to a strict forward cascade has also been detected with a critical transition behaviour.…”
Section: Introductionmentioning
confidence: 98%
“…The influence of discreetness on the turbulent distribution in the system of waves on the liquid hydrogen surface was studied before in [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…In a system of gravity waves formation of the both direct and inverse cascades is possible and the wave energy could be directed into both high and low frequency domains. From our experiment and subsequent numerical simulations [5][6][7] it follows that in a finite size cell, where the spectrum of the wave excitations is discrete, one might observe an energy flow from the pumping region towards both high and low frequency domains even for capillary waves. It should be mentioned that in all the numerical simulations the authors preferred to use asymptotic approximations,…”
Section: δ < ∆ωmentioning
confidence: 99%
“…Detailed method of registration of surface elevations is given in [5]. Any variations of the angle between the gliding laser beam and the oscillating surface led to modulation of the power of the reflected beam.…”
Section: Experimental Techniquementioning
confidence: 99%